Influence of Mounting Incline and Natural Environmental Factors on Pin-Type Silicone Rubber Insulator Leakage Currents Using Internet-Based Monitoring - Waluyo; Muhammad Syah Putra (IEEE Access, 2023)
High-voltage insulators are essential components in overhead transmission and distribution lines. Various environmental factors and probable mounting inclines may influence the performance of insulators. Therefore, it is necessary to continuously and simultaneously investigate these influences using an internet-based data-logging system. Here, the test samples were vertical, thirty-degree, sixty-degree, and horizontal mounting inclinations on 7.5 kV-subjected pin-type silicone rubber (SiR) insulators. The recorded data included 7,917 measurements acquired every five minutes for a month and then analyzed using statistical tools. At midday, the surrounding environmental temperature, illuminance, and ultraviolet (UV) radiation reached their peak values, whereas the humidity reached its lowest value. The air pollution concentration reached its highest levels in the morning, and rain rarely occurred. The insulator leakage currents reached their top values before dawn and their lowest values at midday. Originally, the typical highest leakage current was the vertical mounting insulator, which reached 1.36 up to 2.36 times that of the remaining insulators; the maximum and maximum typical values were $24.27~\mu \text{A}$ and $4.9~\mu \text{A}$ , respectively. Increasing illuminance, UV radiation, and temperature influenced the leakage currents to decrease, but the corresponding leakage currents rose as the humidity, air pollution concentration, and rainfall increased. Based on extrapolations of the data, the vertical mounting insulator is the most vulnerable installation for severe air pollution concentrations, reaching a predicted warning condition of $287.2~\mu \text{g}/\text{m}^{3}$ . However, the horizontal mounting insulator is the least suitable for rainfall above 16.86 mm. The typical shortest forecasted warning condition is 10.3 years on the thirty-degree mounting insulator.